Guided Bone Regeneration: A novel approach to 3D-printed biodegradable meshes (Transactions on Additive Manufacturing Meets Medicine, 2025)
Guided Bone Regeneration (GBR) is a standard surgical procedure to augment jawbone volume, conventionally using titanium meshes or collagen membranes - each with inherent limitations such as stress shielding, imaging artifacts, or insufficient mechanical stability. Here, we introduce a novel 3D-printed, patient-specific biodegradable mesh fabricated via Arburg plastic freeforming (APF) using PLDLLA/?-TCP composite. Three design variants were fabricated: A solid configuration for maximal strength, a porous structure (50% infill) to minimize fibrous tissue ingrowth, and a gyroid design to promote angiogenesis. Our results demonstrate high dimensional accuracy (
Keywords: Oral- and Maxillofacial Surgery; 3D printing; Guided Bone Regeneration; Bioresorbable; patient specific implant